Book Review - Making Muslim Women European - Jelena Gajic (Slovo, 2022)
Book review of Fabio Giomi's Making Muslim Women European: Voluntary Associations, Islam, and Gender in Post-Ottoman Bosnia and Yugoslavia (1878-1941).